2010
DOI: 10.1111/j.1365-2842.2010.02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival rate and potential influential factors for two transitional implant systems in edentulous patients: a prospective clinical study

Abstract: The aim of this present study was to evaluate the success of immediately loaded transitional implants and to identify possible influential factors. A total of 64 patients were recruited in a private specialist implant practice. Two different implant systems were evaluated (IPI, Nobel Biocare, Sweden; I-Plant, Unor, Switzerland). Primary stability, survival rate, gender, location, the type of prosthetic restoration and the tooth status of the opposite jaw were analysed using Kaplan-Meier or Pearson Chi-Square t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Although it has been suggested that failure rate increases as age increases because of decreased bone density caused by bone resorption exceeding osteogenesis25, there was no increased risk related to age in this study as well as in the study of Smith et al26. There was no difference in risk between males and females, as previously determined by Heberer et al27. Renouard and Nisand28 reported that, by avoiding countersink or under-preparation at sites where the bone substance was poor, there was no difference in the success rate between rough-surface implants that were greater than 10 mm and less than 10 mm.…”
Section: Discussionsupporting
confidence: 54%
“…Although it has been suggested that failure rate increases as age increases because of decreased bone density caused by bone resorption exceeding osteogenesis25, there was no increased risk related to age in this study as well as in the study of Smith et al26. There was no difference in risk between males and females, as previously determined by Heberer et al27. Renouard and Nisand28 reported that, by avoiding countersink or under-preparation at sites where the bone substance was poor, there was no difference in the success rate between rough-surface implants that were greater than 10 mm and less than 10 mm.…”
Section: Discussionsupporting
confidence: 54%
“…The total survival was 82% but primary stability appeared to be a significant factor in implant survival. However, gender, type of suprastructure, tooth status of the antagonistic jaw and implant location did not affect their survival . The importance of primary stability was also obvious from the results of a study, based on removal torque tests, that used four provisional implants in 31 patients .…”
Section: Immediate Loading Of Complete Fixed Prosthesesmentioning
confidence: 99%
“…Most of the time, these successes should be related to a multifactorial condition, including the quality and quantity of bone at the recipient site (associated with the immediate stabilization process), accurate treatment planning, proper oral hygiene, and, not less important, the characteristics of the implants and components used for restoration (Heberer et al. ).…”
mentioning
confidence: 99%